Spatial and temporal expressions of two distinct oleate desaturases from olive (Olea europaea L.) - Banilas, Georgios; Moressis, Anastassios; Nikoloudakis, Nikolaos; Hatzopoulos, Polydefkis (My University, 2005)
Two cDNAs, OeFAD2 and OeFAD6, encoding ω-6 fatty acid desaturases, the key enzymes for the conversion of oleic into linoleic acid, were isolated from olive. OeFAD2 contains a C-terminal ER retrieval motif, whereas OeFAD6 possess a putative N-terminal plastidial signal peptide. The deduced amino acid sequence of OeFAD2 showed higher similarities to other plant microsomal ω-6 desasurases than to OeFAD6 or plastidial orthologues, and vice versa. Southern analysis indicated that the OeFAD2 gene is represented by one or two copies and OeFAD6 by a single copy gene. Expression analysis by RT-PCR showed that both genes are expressed in all tissues of olive tree tested, but higher levels of mRNA accumulation were detected in reproductive organs and cells that proliferate rapidly or store lipids. The two genes exhibited distinct patterns of mRNA accumulation during olive drupe growth. OeFAD2 was constitutively expressed, with maximum transcript accumulation in mesocarps, whereas OeFAD6 was developmentally regulated in both endosperms and embryos. The expression patterns observed reflect the discrete roles of these genes in membrane synthesis for cell division, thylakoid development, and lipid storage or in the biosynthetic pathway for the production of signaling molecules that influence plant development or defense. © 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: FAD2; FAD6; Fatty acid desaturase; Olive; Spatial expression; Temporal expression